Is This Within Reach? Left but Not Right Brain Damage Affects Affordance Judgment Tendencies - Randerath, Jennifer; Finkel, Lisa; Shigaki, Cheryl; Burris, Joe; Nanda, Ashish; Hwang, Peter; Frey, Scott H. (Frontiers in Human Neuroscience, 2021)
The ability to judge accurately whether or not an action can be accomplished successfully is critical for selecting appropriate response options that enable adaptive behaviors. Such affordance judgments are thought to rely on the perceived fit between environmental properties and knowledge of one’s current physical capabilities. Little, however, is currently known about the ability of individuals to judge their own affordances following a stroke, or about the underlying neural mechanisms involved. To address these issues, we employed a signal detection approach to investigate the impact of left or right hemisphere injuries on judgments of whether a visual object was located within reach while remaining still (i.e., reachability). Regarding perceptual sensitivity and accuracy in judging reachability, there were no significant group differences between healthy controls (N = 29), right brain damaged (RBD, N = 17) and left brain damaged stroke patients (LBD, N = 17). However, while the groups of healthy controls and RBD patients overestimated their reach capability, LBD patients’ average response criterion converged to zero, indicating no judgment tendency. Critically, the LBD group’s response criterion pattern is consistent with previous findings in this same sample on an affordance judgment task that required estimating whether the hand can fit through apertures (Randerath et al., 2018). Lesion analysis suggests that this loss of judgment tendency may be associated with damage to the left inferior parietal lobe and middle temporal lobe. Based on these results, we propose that damage to the left ventro-dorsal stream disrupts the retrieval and processing of a stable criterion, leading to stronger reliance on intact on-line body-perceptive processes computed within the preserved bilateral dorsal network.